Isotopic analysis of the Blick Mead dog: A proxy for the dietary reconstruction and mobility of Mesolithic British hunter-gatherers. (April 2019) - Rogers, B.; Gron, K.J.; Montgomery, J.; Rowley-Conwy, P.; Nowell, G.; Peterkin, J.; Jacques, D.
Abstract: A single domestic dog ( Canis familiaris ) tooth was recovered from the Mesolithic site of Blick Mead in the Stonehenge landscape. As no human remains were recovered from the site, the dog tooth provides a potential proxy for reconstructing human diet. Previous studies have shown that domestic dogs often have similar δ 13 C and δ 15 N values to their human companions. Incremental dentine carbon and nitrogen isotope analysis and bulk enamel carbon, oxygen and strontium isotope analysis were obtained from the tooth to produce a life-history profile of the dog's diet and mobility. The δ 13 C and δ 15 N values indicate that there was little variation in the dog's diet between c.2 and 6 months of age. δ 15 N values range between +7.9 to +8.7‰, (mean +8.5‰), whereas δ 13 C values range between −21.3 and −20.5‰, (mean −20.9‰). These data suggest that the dog was consuming predominantly terrestrial herbivorous protein, with the possible inclusion of freshwater fish. The enamel 87 Sr/ 86 Sr ratio of 0.70796 can only be obtained from a chalk landscape, such as is found at Blick Mead and elsewhere in southern and southeastern Britain, or basalt terrains which are rare in southern Britain. The enamel δ 18 O(SMOW) value of 25.7‰ is not consistent with the dog residing at Blick Mead but appropriate contemporaneous data from dogs is currently lacking. The results are thus consistent with the dog originating in a chalk or possibly basaltic terrain elsewhere in Britain and Ireland or that the dog resided locally at a time when the climate was colder than present. Highlights: The dog had a terrestrial diet with the possible inclusion of freshwater fish. The Sr results (0.70796) are consistent with the dog being local to the site. The δ 18 O value (25.7‰) is not consistent with the dog being local to the site.